Medios de comunicación radial y su relación con la opinión pública del Recinto El Descanso, Cantón Buena Fe Provincia de Los Ríos - Cedeño Gonzalez, Angie Mabel (2019)
It is interesting to evaluate that in the middle of the twenty-first century with all the technological reach and advantages that exist in front of the radio, Ecuadorians still retain radio transmission devices and tune in to the different stations that they have, I know how to inform themselves, listen to music, sports, programs of opinion which is ironic because currently there are audiovisual media that offer live images, entertainment for all ages, this same technology with all the sophistication has not yet been able to disappear the electromagnetic radiation waves that still retain a good acceptance by young and old in homes and that it is very far for this to end because radio has been able and able to adapt to the new century and the challenges that these entail. Undoubtedly, the new technological advances have the ability to reach and capture the attention of the consumer, but the radio does not lag behind its ability to analyze and target the entire public of the new and old generation that does not adapt to technology It is essential, international frequencies have worked strategically with technology other radio and television frequencies to provide effective information according to the expectations of the radio listener who searches even on the radio what he does not find on satellite television or smartphones such as It is usually called. In the enclosure the rest its inhabitants indicate that there is no coverage of the local news despite the fact that the communiqués that the local authorities make about arrangements or suspension of some basic service are prepared to be prepared, it does not have to know because the media Local communication is repeated once or twice and they continue with their already established programming generating discomfort in the inhabitants not only of the El Descanso site but also a general discontent of the other neighboring sectors